Phase i clinical trialto evaluate the pharmacokinetics, safety, and tolerability of one intramuscular injection of risperidone ISM® at different dose strengths in subjects with Schizophrenia or Schizoaffective disorder (PRISMA-1) - Llaudó, J.; Ayani, I.; Monreal, M.; Martínez-González, J.; Gutierro, I. (Clinical therapeutics, 2015)
A clinical trial was conducted to characterize the pharmacokinetics and to evaluate the safety of Risperidone ISM® in subjects with schizophrenia or schizoaffective disorder (ClinicalTrials.gov identifier: